Foot Print in the Rheumatoid Foot - Yamamoto, Kichizo; Okuno, Makoto; Hagino, Hiroshi; Teshima, Ryota; Otsuki, Takeo (Orthopedics & Traumatology, 1997)
Footprints of 16 patients with rheumatoid arthritis (32 feet) and 12 normal subjects (24 feet) were recorded using a pressure distribution measurement system (ANIMA MP-4800) during gait and static double standing. 14 feet of 32 rheumatoid feet had callus plantar forefoot. Arch index was calculated from the recorded foot print images. In rheumatoid feet with callus, the difference between arch index during gait and arch index while standing is significantly decreased compared with that of normal subjects. These results suggest that flexibility of the arch is decreased in rheumaoid feet with callus formation.